Explication of the metaphysical foundations of the modern age in Heidegger's secondary literature - Grbić Safer (Kom: Časopis za Religijske Nauke)
In this work, and in line with the attention international researchers have devoted to Heidegger's major works to contribute to the elucidation of his teachings, we intend to establish a hypothesis based on Heidegger's secondary literature in his thought-following his speeches, presentations, lectures, letters, notes, interviews, etc. Thus, the hypothesis of this work aims to prove the foundation of Heidegger's teachings on the Metaphysical Foundations of the Modern Age-specifically, by posing questions on the Essence of Modern Age Science, the Essence of Action in the Modern Age, and the Essence of Technic in the Modern Age. In this context, this essay explores the main phenomena of modernity emphasized by Heidegger in his secondary works to demonstrate the Metaphysical Foundations of the Modern Age and thereby prove the Metaphysical Foundation of the Modern Age's essence of Modern Age science, the essence of action in the Modern Age, and the essence of technic in the Modern Age. The ultimate goal is to synthesize fragments from various Heideggerian works of secondary literature to point out, in one place, what Heidegger taught at a higher level in his major works: how the Modern Age, in all its fundamental phenomena and in the entirety of its richness/deficiencies, delivers its foundations within Modern Age Metaphysics.